The novel manualized RELIEVE-group treatment for burdened relatives of cancer patients: a feasibility study - Neumann, Jessica; Beckord, Jil; Hesse, Helen Samira; Martin, Carl; Mons, Carlotta; Chur, Diana; Hense, Jörg; Tewes, Mitra; Teufel, Martin; Skoda, Eva-Maria (Frontiers in Psychology, 2025)
IntroductionThe experience of cancer among relatives is characterized by an increase in anxiety and depression, stress, and a reduction in quality of life. However, there is a paucity of psychosocial support programmes for relatives and a dearth of evidence-based, manualized interventions. Accordingly, the present study aims to assess the acceptability, defined as participant drop-out and satisfaction, and feasibility, in terms of mental health improvement, of a novel manualized psycho-educational group intervention.MethodsThe manual was developed on the basis of previous research into psychotherapy. A total of 33 relatives of cancer patients were recruited from the West German Tumor Center and participated in the five modules of the RELIEVE treatment which included an introduction, communication skills, stress and anxiety management and self-care. The primary outcome was assessed using a range of measures, including anxiety (GAD-7), depression (PHQ-8), stress (PSQ), self-efficacy (SES), need for support (SCNSP&C-G), and quality of life (WGOQOL-BREF) before and after the completion of the treatment programme. A paired samples T-test was employed to assess the feasibility of the treatment, with pre- and post-scores being compared. The secondary outcome of treatment acceptance was evaluated by calculating the drop-out rate and scoring a treatment satisfaction questionnaire.ResultsA high level of satisfaction was reported by participants. The drop-out rate for the treatment was minimal, at only 2.86%. Following the completion of the treatment programme, there were significant improvements in anxiety, depression and stress scores, as well as an improvement in quality of life. No significant improvements were observed in self-efficacy, work and social security needs, and quality of life in the social relationships domain.DiscussionThe RELIEVE intervention demonstrated high feasibility and acceptance among emotionally affected relatives of cancer patients, addressing a gap in previous interventions that were often limited in scope and lacked standardised manuals.ConclusionThis feasibility study on treatment acceptance underlines the importance of measures that are tailored to the specific needs of cancer patients’ relatives, and of integrating them into the general healthcare system.